Are experiences of family and of organized violence predictors of aggression and violent behavior? A study with unaccompanied refugee minors. Issue 1 (1st December 2016) - Mueller-Bamouh, Veronika; Ruf-Leuschner, Martina; Dohrmann, Katalin; Schauer, Maggie; Elbert, Thomas
Abstract : Background: There is strong support for familial abuse as a risk factor for later delinquency and violent offending, whereas empirical evidence about the contribution of experienced organized violence to the cycle of violence is less clear. Nevertheless not all abused children do become violent offenders. This raises the question of which factors influence these children's risk of future aggressive behavior. Recent evidence suggests that the trait of appetitive aggression plays an important role in the prediction of aggressive behavior. Objective: The focus of the study is to investigate whether exposures to 1) organized; and 2) family violence equally contribute to aggressive behavior and how this is related to a trait of appetitive aggression. Furthermore it is of interest to uncover how the severity of posttraumatic stress disorder (PTSD) symptoms modulates associations between violent experiences and aggression. Method: To answer these questions, we investigated unaccompanied refugee minors who had been exposed to varying levels of both violence types. Using structured interviews, experiences of organized and familial violence, self-committed aggressive acts, the trait of appetitive aggression, and PTSD symptoms were assessed in 49 volunteers. Results: A sequential regression analysis revealed that the trait of appetitive aggression and experienced family violence were independent and significant predictors of self-committed aggressive acts, altogether accounting for 70% of the variance. Exposure to organized violence, however, was not significantly associated with aggressive acts or appetitive aggression. PTSD symptom severity was not correlated with measures of aggression but with the exposure to familial and organized violence. Conclusions: Results suggest that in addition to the impact of family violence, an elevated trait of appetitive aggression plays a crucial role in aggressive behavior and should be considered in psychotherapeutic treatment.